Ladybirds, Ladybird beetles, Lady Beetles, Ladybugs of Florida, Coleoptera: Coccinellidae - John Howard Frank; Russell F. Mizell, III (EDIS, 2002)
This document is EENY-170, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000. Revised: April 2002.